Decade-long response of arid-land mallee vegetation to fire, flooding and grazing in south-eastern Australia. (October 2015) - Florentine, Singarayer; Milberg, Per; Di Stefano, Julian; Westbrooke, Martin; Graz, Patrick
Abstract: Australian arid vegetation has evolved within highly variable environments characterised by low rainfall and sporadic fire events. Episodic high rainfall events are a significant factor in plant species recruitment, but their unpredictability makes them difficult to study. We report on the response of vascular plants to a major rainfall event and flood in an arid region of south-eastern Australia. Fire that occurred two months before the flood was incorporated into the study. Paired fenced and unfenced plots were established at control locations and also in areas that had been either flooded, burnt, or flooded and burnt. Objectives were to quantify the long-term effects of fire, flood and vertebrate herbivory, and their interactions, on vegetation composition, plant life forms and species diversity. We found that relative to controls (i) there was a significant effect of flooding on vegetation composition, (ii) changes in life form abundance were driven by flooding and grazing, (iii) there was a strong positive relationship between grazer exclusion and species diversity that was maintained over time and (iv) there was little effect of fire. Understanding the long-term effects of both natural disturbances and vertebrate herbivory will benefit plant conservation in the arid zone. Highlights: Vegetation composition changed profoundly in plots that had been flooded. Grazer exclusion lead to persistently higher species diversity. Fire had small to no effect on vegetation composition. Grasses as well as exotic species increased in flooded plots.